2022
DOI: 10.1007/s00586-022-07331-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of multi-rod constructs by satellite rod configurations (in-line vs. lateral) and screw types (monoaxial vs. polyaxial) spanning a lumbar pedicle subtraction osteotomy (PSO): is there an optimal configuration?

Abstract: Purpose Multi-rod constructs are used commonly to stabilize pedicle subtraction osteotomies (PSO). This study aimed to evaluate biomechanical properties of different satellite rod configurations and effects of screw-type spanning a PSO. Methods A validated 3D spinopelvic finite element model with a L3 PSO (30°) was used to evaluate 5 models: (1) Control (T10–pelvis + 2 rods); (2) lateral satellite rods connected via offsets to monoaxial screws (LatSat-Mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated that multi-rod constructs across lumbar PSOs provide more robust biomechanical environments and decrease rod fracture fractures relatively to 2-rod constructs [ 14 23 ]. Creating multi-rod constructs across S1-PSOs can be more challenging given the relatively limited space/anatomy as well as limited available osseous fixation points distal to S1 (i.e., in the sacrum and pelvis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated that multi-rod constructs across lumbar PSOs provide more robust biomechanical environments and decrease rod fracture fractures relatively to 2-rod constructs [ 14 23 ]. Creating multi-rod constructs across S1-PSOs can be more challenging given the relatively limited space/anatomy as well as limited available osseous fixation points distal to S1 (i.e., in the sacrum and pelvis).…”
Section: Discussionmentioning
confidence: 99%
“…The size and length of the pedicle screws were consistent in all models. Polyaxial screws were simulated using a methodology presented in the literature [ 14 , 27 ]. The primary (PR), accessory (AR), and horizontal rods (HR) were tied to the tulip in all the models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation